(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Recurrent periods of mania, hypomania, mixed moods, and depression characterize bipolar disorder, which is a chronic psychiatric illness. The prevalence of bipolar disorder has been estimated to be between 1% and 2% in various researches. According to the National Comorbidity Survey, the lifetime prevalence is 1.6 percent. Many community survey estimates may not include milder types of bipolar illness, resulting in an underestimating of the true prevalence of the disorder's spectrum. Bipolar illness affects both men and women at similar rates. Over the course of the illness, women appear to be more prone to have mostly depressive rather than manic symptoms. At any age, bipolar disorder (BD) can appear for the first time. According to a survey conducted by the National Depressive and Manic-Depressive Association (NDMDA), 59 % of patients with bipolar disorder first developed symptoms during childhood or adolescence. Bipolar disorder, on the other hand, can appear later in life for the first time. Even with continued treatment, recurrence rates for bipolar disorder remain significant. A 5-year relapse rate of 73 % was discovered in one study, with two-thirds of the patients experiencing numerous relapses. According to other estimates, the relapse rate is around 90%, with approximately half of all relapses happening within two years. The objective of the study is to determine the prevalence of relapse rate of bipolar disorder. The relapse rate in our study was further evaluated on the basis of total numbers of relapse occurred in one year, two years, three years, four years and five years respectively. The result showed that the mean number of relapses in one year was 1.78 ± 1.03 times; in two years was 2.25 ± 0.46 times, in three years 2.64 ± 0.90 times, in four years 3.69 ± 0.837 times and in five years it was found to be 4.24 ± 0.830 times respectively. There was no significant relationship found between relapse rate with gender, marital status, compliance of drug and distribution of age respectively. However, there was significant relationship was found between employment statuses of patients with relapse. (pvalue=0.024*).The healthcare sector faces a big difficulty with bipolar disorder. Misdiagnosis is widespread, and the illness may be more common than previously assumed. Even with continuing treatment, recurrence rates are significant. Bipolar disorder has a wide range of effects on a person's life. Patients with bipolar disorder have a high likelihood of unemployment, and they often struggle in the workplace as well as in social and personal interactions. Bipolar illness patients have a high rate of psychiatric and medical comorbidity, which leads to a higher use of healthcare resources.